PEMBUATAN PERANGKAT PEMBELAJARAN SAINS TERPADU PADA MATA PELAJARAN IPA SMP KELAS VII - Nesha Resty Aufiana; Festiyed Festiyed; Yurnetti Yurnetti (Universitas Negeri Padang, 2015)
Learning science on Junior High School emphasized in integrated form which called by Integrated Science. Based on the observations, generally teachers are still experiencing difficulties in learning a whole load of material. One of solution that can be done is to design the Integrated Science Learning Devices which includes lesson plans, handouts, and worksheets. Under these conditions, the purpose of this research is to produce learning devices and determine the validity, practicalities and effectiveness of the Integrated Science Learning Devices in science subject of Junior High School grade VII. The type of this research is Research and Development. There are two objects in this research, including the Integrated Science Learning Devices in science subjects dan 27 people of seventh grade students. The result of this research are: first, the learning devices has high validity. Second, the design of Integrated Science Learning Devices are lesson plan, handout and worksheet. Third, the learning devices are practical for student and science teacher. And last, the learning devices are proven effective to increase student learning result